1990
DOI: 10.1002/1097-0142(19901201)66:11<2369::aid-cncr2820661120>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Growth-inhibitory effects of combination chemotherapy for human pancreatic cancer cell lines

Abstract: Sensitivities to anti-tumor drugs, mytomycin C (MMC), aclarubicin hydrochloride (ACR), doxorubicin hydrochloride (ADR), cisplatin, and 5-fluorouracil(5FU), were examined using PK-1, -8, -9, -12, -14, and -16 cell lines derived from human pancreatic cancer. These cell lines showed different sensitivities to each of the above anti-tumor drugs. The concentrations required for 50% growth-inhibition (ICJ after 2 hours of exposure were 0.096 to 0.35 pg/ml for MMC, 0.0074 to 0.0076 pg/ml for ACR, 0.033 to 0.23 pg/ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Similar concentrations for chemotherapeutic drugs and treatment schedules were used in vitro by other authors, e.g. for 5-FU [51], mitomycin C [52] or oxaliplatin [53]. Interestingly, we found that 5-FU, mitomycin-C and oxaliplatin at the concentrations tested up-regulated distinctly EpCAM and Lewis Y antigen expression.…”
Section: Discussionsupporting
confidence: 84%
“…Similar concentrations for chemotherapeutic drugs and treatment schedules were used in vitro by other authors, e.g. for 5-FU [51], mitomycin C [52] or oxaliplatin [53]. Interestingly, we found that 5-FU, mitomycin-C and oxaliplatin at the concentrations tested up-regulated distinctly EpCAM and Lewis Y antigen expression.…”
Section: Discussionsupporting
confidence: 84%
“…Anderson Cancer Center, Houston, TX, April 2009). Based on previously reported (Matsuno et al 1990) and confirmed inhibitory concentrations, doxorubicin (Bedford Laboratories, Bedford, OH) was diluted to 0.02 ÎŒg/mL in complete DMEM and the cells were treated 24 h after plating while control cells were treated with equivolume phosphate-buffered saline instead of doxorubicin.…”
Section: Protocolmentioning
confidence: 85%
“…These included data for cisplatin/paclitaxel (18–21), cisplatin/docetaxel (18), carboplatin/paclitaxel and carboplatin/docetaxel (22). An additional 21 data sets for a variety of drug combinations were collected: 5-fluorouracil/aclarubicin hydrochloride (23); 5-fluorouracil/fleroxacin (24); 5-fluorouracil/mitomycin-C (23); acivicin/asparaginase (25); aclarubicin hydrochloride/mitomycin-C (23); cyclophosphamide and thiotepa (26); erlotinib/rapamycin (27); gemcitabine/TRA-8 (28); imatinib/rapamycin (29); trastuzumab/ZD1839 (30) (31); gemcitabine/OBP-301(32). Cell lines used for these data cells were: A549 (human lung adenocarcinoma); B2-2 (biliary tract); Ba/F-BCR/ABLWT and Ba/F-BCR/ABL T315I (variants of the Ba/F3 murine hematopoietic cell line); BT-474 (human mammary); EMT6 (mouse mammary); MBT-2 (mouse bladder carcinoma); MCF-7 (human mammary); MIA-PaCa-2 (pancreatic); NCI-H23 (lung); PK-1 and PK-8 (human pancreatic); S2-VP10 (subline of a human pancreatic SUIT-2), SK-Br-3 (human mammary); T-24 (human bladder carcinoma); TE-671 (human medulloblastoma); H322 (human lung cancer).…”
Section: Methodsmentioning
confidence: 99%